First, we will prove the base case for n = 1:
When n = 1, the left side of the equation is 1^2 = 1.
Plugging n = 1 into the right side of the equation, we get:
1(1 + 1)(2(1) + 1)/6 = 1(2)(3)/6 = 6/6 = 1.
Since the left side and the right side both equal 1 when n = 1, the base case is true.
Now, we assume that the equation holds for some positive integer k, where k β₯ 1:
1^2 + 2^2 + 3^2 + ... + k^2 = k(k + 1)(2k + 1)/6.
We will prove that the equation also holds for k + 1:
1^2 + 2^2 + 3^2 + ... + k^2 + (k + 1)^2 = (k + 1)[(k + 1) + 1][2(k + 1) + 1]/6.
Starting with the left side:
1^2 + 2^2 + 3^2 + ... + k^2 + (k + 1)^2 = k(k + 1)(2k + 1)/6 + (k + 1)^2.
Multiplying both terms by 6:
6[k(k + 1)(2k + 1)/6 + (k + 1)^2] = k(k + 1)(2k + 1) + 6(k + 1)^2.
Expanding the multiplication:
k(k + 1)(2k + 1) + 6(k + 1)^2 = 2k^3 + 3k^2 + k + 6k^2 + 12k + 6.
Combining like terms:
2k^3 + 9k^2 + 13k + 6.
Factoring out a common factor of 2:
2(k^3 + 4.5k^2 + 6.5k + 3).
Factoring the cubic term:
2(k + 1)(k + 2)(k + 3).
Now, we have:
2(k + 1)(k + 2)(k + 3).
We can rewrite the right side of the equation as:
(k + 1)((k + 1) + 1)(2(k + 1) + 1)/6.
This is equal to:
(k + 1)(k + 2)(2k + 3)/6.
Therefore, we have shown that:
1^2 + 2^2 + 3^2 + ... + k^2 + (k + 1)^2 = (k + 1)(k + 2)(2k + 3)/6.
By the principle of mathematical induction, the statement is true for all positive integers n.
1. Prove that 1^2+ 2^2+ 3^2 + β― + π^2 = π(π+1)(2π+1)Γ·6, βππ β β by using the principle of
mathematical induction
1 answer